2006
DOI: 10.1507/endocrj.kr-74
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and Regeneration of Adrenal Tissues: An Initial Step toward Regeneration Therapy for Steroid Insufficiency

Abstract: Abstract. In animal experiments, adrenal cortical tissue has been successfully regenerated through xenotransplantation of cloned adrenocortical cells, suggesting that the intraadrenal stem cells required for such tissue formation may be present in the adrenal cortex. Stable expression of Ad4BP/SF-1, a key factor for adrenal and gonadal development and steroidogenesis, has been shown to direct embryonic stem cells toward the steroidogenic lineage. However, this steroidogenic capacity was very limited since prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 57 publications
(70 reference statements)
2
18
0
Order By: Relevance
“…As in mouse cells (Gondo et al 2004), the steroid profile of cultured human BMCs showed a mixed pattern of adrenal and gonadal steroidogenesis, namely the simultaneous production of cortisol and sex steroids. This finding matches well an established concept that common precursor cells divide into two distinct characteristic cell types, designated adrenal precursor cells and bipotential gonadal precursor cells, and finally develop into the adrenal cortex or testes and ovaries, respectively, under the regulation of many transcriptional factors, including SF-1 (Yanase et al 2006).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As in mouse cells (Gondo et al 2004), the steroid profile of cultured human BMCs showed a mixed pattern of adrenal and gonadal steroidogenesis, namely the simultaneous production of cortisol and sex steroids. This finding matches well an established concept that common precursor cells divide into two distinct characteristic cell types, designated adrenal precursor cells and bipotential gonadal precursor cells, and finally develop into the adrenal cortex or testes and ovaries, respectively, under the regulation of many transcriptional factors, including SF-1 (Yanase et al 2006).…”
Section: Discussionsupporting
confidence: 90%
“…In humans, sex-determining region Y (SRY) initiates the testis-determining pathway by inducing the expression of a series of downstream factors, including SF-1, WT1, DAX-1, SRY-related genes HMG-box 9, and several other factors, thus resulting in a male phenotype (Yanase et al 2006). In this pathway, SF-1 has been considered to be a master regulator that controls the overall stream of the developmental mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method can also differentiate human BM-MSCs into cortisol-producing cells in response to adrenocorticotropic hormone stimulation, which are similar to the zona fasciculata cells of the adrenal gland. Additionally, BM-MSCs transform to steroidogenic cells by adenovirus-mediated transient expression of SF-1 Tanaka et al, 2007;Wei et al, 2012;Yanase et al, 2006). These studies are consistent with the concept that SF-1 is a master regulator for steroidogenesis.…”
Section: Differentiation Of Stem Cells Into Steroidogenic Cells By Sfsupporting
confidence: 84%
“…Some evidence that MSCs could differentiate to steroidogenic cells was obtained via transplantation of bone marrow MSCs into the testis (Yazawa et al 2006). Human and mouse MSCs, derived from bone marrow or fat, become capable of expressing steroidogenic genes and of synthesizing several steroids following forced expression of SF-1 or LRH-1 (NR5A2; Yanase et al 2006, Tanaka et al 2007, Gondo et al 2008, Yazawa et al 2009). Importantly, forced expression of SF-1 in mesenchymal cells produced cells capable of secreting DHEA as well as other adrenocortical steroids (Tanaka et al 2007, Gondo et al 2008.…”
Section: Potential Studies On Differentiation Of Pluripotent Cellsmentioning
confidence: 99%